Uncertainties in the relationship between atmospheric nitrogen deposition and forest carbon sequestration - SUTTON, MARK A.; SIMPSON, DAVID; LEVY, PETER E.; SMITH, ROGNVALD I.; REIS, STEFAN; Van OIJEN, MARCEL; De VRIES, WIM (Global change biology, 2008)
In a recent study, Magnani et al. report how atmospheric nitrogen deposition drives stand‐lifetime net ecosystem productivity (NEPav) for midlatitude forests, with an extremely high C to N response (725 kg C kg−1 wet‐deposited N for their European sites). We present here a re‐analysis of these data, which suggests a much smaller C : N response for total N inputs. Accounting for dry, as well as wet N deposition reduces the C : N response to 177 : 1. However, if covariance with intersite climatological differences is accounted for, the actual C : N response in this dataset may be <70 : 1. We then use a model analysis of 22 European forest stands to simulate the findings of Magnani et al. Multisite regression of simulated NEPav vs. total N deposition reproduces a high C : N response (149 : 1). However, once the effects of intersite climatological differences are accounted for, the value is again found to be much smaller, pointing to a real C : N response of about 50–75 : 1.